2001
DOI: 10.1139/gen-44-1-50
|View full text |Cite
|
Sign up to set email alerts
|

Development of microsatellite markers in potato and their use in phylogenetic and fingerprinting analyses

Abstract: Three genomic libraries were constructed using a mixture of DNA from Solanum phureja Juz. & Buk., and S. chacoense Bitt. Two of the libraries were enriched for ATT and GT repeats (a 27-fold enrichment was achieved). In total, 3500 clones of the conventional library, 1,000 of the library enriched for ATT, and 12,000 of the one enriched for GT were screened with five different repeat motifs, and a total of 18 primer pairs was obtained. Another group of 12 primer pairs was obtained from the SSR-containing sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 0 publications
4
16
0
1
Order By: Relevance
“…These factors might account for the relatively low level of polymorphism revealed overall, 39%, in comparison with other recent studies using microsatellites that revealed polymorphism rates as high as 93% for lettuce (van de Wiel et al 1999) and coconut (Rivera et al 1999). However, the level of polymorphism revealed between taro genotypes by the microsatellites generated in this study is comparable with a recent study carried out on potato, also a vegetatively propagated root crop, where microsatellites revealed a polymorphism rate of just 33.3% (Ashkenazi et al 2001) and also in olive tree (Rallo et al 2000) with a polymorphism rate of just 38.4%, which, like taro, has been traditionally bred through clonal and (or) varietal selection. Therefore, the low levels of polymorphism revealed in this study may be a consequence of the prolonged period of clonal propagation that taro has undergone in Southeast Asia and Oceania, rather than a reflection of the nature of the repeat types isolated.…”
Section: Discussionsupporting
confidence: 79%
“…These factors might account for the relatively low level of polymorphism revealed overall, 39%, in comparison with other recent studies using microsatellites that revealed polymorphism rates as high as 93% for lettuce (van de Wiel et al 1999) and coconut (Rivera et al 1999). However, the level of polymorphism revealed between taro genotypes by the microsatellites generated in this study is comparable with a recent study carried out on potato, also a vegetatively propagated root crop, where microsatellites revealed a polymorphism rate of just 33.3% (Ashkenazi et al 2001) and also in olive tree (Rallo et al 2000) with a polymorphism rate of just 38.4%, which, like taro, has been traditionally bred through clonal and (or) varietal selection. Therefore, the low levels of polymorphism revealed in this study may be a consequence of the prolonged period of clonal propagation that taro has undergone in Southeast Asia and Oceania, rather than a reflection of the nature of the repeat types isolated.…”
Section: Discussionsupporting
confidence: 79%
“…In beans, Yu et al (2000) identified SSR primers from Vigna aconitifolia, a distantly related species, which amplified Phaseolus vulgaris DNA. Ashkenazi et al (2001) identified SSR markers obtained from tomato capable of producing PCR products from the potato genome.…”
Section: Discussionmentioning
confidence: 99%
“…Additional advantages of SSR markers over dominant marker systems are their high heterozygosity and capacity to reflect ploidy status in potato (Ghislain et al 2004). Many researchers have therefore developed potato SSR markers from genomic libraries and expressed sequence tags (ESTs) databases (Milbourne et al 1998;Ashkenazi et al 2001;Ghislain et al 2004;Feingold et al 2005;Ghislain et al 2009). These markers have been extensively used for DNA fingerprinting (Norero et al 2002;Coombs et al 2004;Barandalla et al 2006;Karaagac et al 2014;Bali et al 2017), genetic diversity analysis (Chimote et al 2004;Ispizúa et al 2007), germplasm migrations (Ríos et al 2007), and parental analysis (Spanoghe et al 2015) in potato.…”
Section: Introductionmentioning
confidence: 99%